Copper-Catalyzed Synthesis of Substituted 4-Acylpyrazole Derivatives through a Cascade Transformation from N-Propargylic Sulfonylhydrazones and Diaryliodonium Salts - Li, Ren-Hao; Fan, Xin-Yang; Hu, Zi-Lin; Liu, Zhi-Kai; Yang, Ying; Tang, Hai-Tao; Chen, Yi-Hui; Chen, Li; Zhan, Zhuang-Ping (Synlett, 2018)
A concise strategy for the synthesis of substituted 4-acylpyrazole derivatives from N-propargylic sulfonylhydrazones and diaryliodonium salts has been developed. The pyrazole derivatives are formed through a five-step cascade sequence that includes intramolecular cyclization, hydroxylation, elimination, copper-catalyzed aerobic oxidation, and intramolecular rearrangement.
Keywords: propargylic sulfonylhydrazones; diaryliodonium salts; cascade transformation; acylpyrazoles